2009
DOI: 10.1590/s0103-05822009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Introdução alimentar e anemia em lactentes do município de Campinas (SP)

Abstract: OBJETIVO: Verificar a prevalência de anemia em crianças do município de Campinas, levando-se em consideração a introdução de alimentos complementares. MÉTODOS: Estudo transversal realizado com 354 crianças de seis a 12 meses de idade, sorteadas do Sistema de Informações de Nascidos Vivos da cidade de Campinas. Profissionais da área da saúde devidamente treinados realizaram entrevista domiciliar com as mães dos lactentes, as quais responderam a um questionário contendo dados sobre a introdução de alimentos e co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Jaime et al 20 , who evaluated data from the National Health Survey, found that 1/3 of the Brazilian infants under two years old had consumed soft drinks, while 60.8% had consumed cookies, crackers, or cakes, and found that infants in the Southeast presented higher prevalence of consumption of such food than the country as a whole. The consumption of UPF is harmful to a child's health and may be associated with ane-mia, overweight, chronic non-communicable diseases, and food allergies 4,[21][22][23][24] , as well as high amounts of sodium, sugar, fats, and artificial additives 5,6 . In addition, FV are sources of vitamins and minerals, which are essential for the proper development and supply an organism with fibers and water, helping to maintain health 2,4 . Step 7 of the Dietary Guidelines for children under two years old -based on the World Health Organization guidelines -recommends that daily consumption of FV should be stimulated beginning at six months old.…”
Section: Discussionmentioning
confidence: 99%
“…Jaime et al 20 , who evaluated data from the National Health Survey, found that 1/3 of the Brazilian infants under two years old had consumed soft drinks, while 60.8% had consumed cookies, crackers, or cakes, and found that infants in the Southeast presented higher prevalence of consumption of such food than the country as a whole. The consumption of UPF is harmful to a child's health and may be associated with ane-mia, overweight, chronic non-communicable diseases, and food allergies 4,[21][22][23][24] , as well as high amounts of sodium, sugar, fats, and artificial additives 5,6 . In addition, FV are sources of vitamins and minerals, which are essential for the proper development and supply an organism with fibers and water, helping to maintain health 2,4 . Step 7 of the Dietary Guidelines for children under two years old -based on the World Health Organization guidelines -recommends that daily consumption of FV should be stimulated beginning at six months old.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes reported in eligible studies were: bone health (14 studies) (Motegi et al, 2001; Heaney et al, 2002; Berberidis et al, 2004; Sorenson et al, 2004; Arslantas et al, 2008; Jha et al, 2010; Uenishi and Nakamura, 2010; Bener and El Ayoubi, 2012; Nasrollahi et al, 2012; Sahni et al, 2012, 2013a,b; Bonjour et al, 2013; Feart et al, 2013), weight management and nutrition-related health outcomes (81 studies) (Jordan et al, 1981; Thompson et al, 1982; Bazzarre et al, 1983; Massey, 1984; McNamara et al, 1989; Sullivan et al, 1989; Rolls et al, 1991, 1994, 1995; Trapp et al, 1993; Vandewater and Vickers, 1996; Oosthuizen et al, 1998; Campbell et al, 1999, 2000; Burns et al, 2000, 2001, 2002; Hoffman et al, 2000; Zandstra et al, 2000; Mensink et al, 2002; Mossavar-Rahmani et al, 2002; O'Donovan et al, 2003; Rodriguez-Artalejo et al, 2003; Chien et al, 2004; Sorenson et al, 2004; King et al, 2005; Rosado et al, 2005; Yae et al, 2005; Zemel et al, 2005; Logan et al, 2006; Nobre et al, 2006; Tsuchiya et al, 2006; Albertson et al, 2007; Dewan et al, 2007, 2009; Diepvens et al, 2007, 2008; Nazare et al, 2007; Snijder et al, 2007; Beydoun et al, 2008; Bonet Serra et al, 2008; Vergnaud et al, 2008; van der Zander et al, 2008; Almiron-Roig et al, 2009; Berkey et al, 2009; Jordão et al, 2009; White et al, 2009; Chapelot and Payen, 2010; Hursel et al, 2010; Keast et al, 2010, 2013; Lluch et al, 2010; Ortinau et al, 2010, 2012a,b, 2013; Pounis et al,...…”
Section: Resultsmentioning
confidence: 99%
“…Currently, bottle feeding is associated with the use of infant formulas offered as a means of supplementing the diet of the newborn. An interdependent relationship can be established between inadequate breastfeeding techniques, the introduction of infant formula and bottle feeding (8)(9)(10)(11)(12)(13)(14) . According to the literature, factors such as low birth weight, prematurity, inadequate breastfeeding techniques, hospitalization, intubation and the use of probes may be associated with some signs of discomfort observed during and after breastfeeding, as it was the case with the population selected for this study (2,3) .…”
Section: Discussionmentioning
confidence: 99%